Development of Digital Archive System Using Website Based and Integrated Scanning in Course Tuition Center - Valenda, Ovela Yusma; Putri, Natasya Adelia; Ratzlaff, Natasya Sabrina Agvi Azriella; Fauzurrohim, Muhammad Humam; Putra, Muhammad Rafi Adriansyah; Sumarsono, Raden Bambang; Wibowo, Wahyu Adi Setyo (Proceedings Series of Educational Studies, 2024)
This research aims to develop a website-based digital archiving system that is integrated with document scanning technology (Integrated Scanning) in a tutoring institution. The methods used include needs analysis, system design, implementation and evaluation. The needs analysis stage is carried out through literature studies and interviews with potential users to understand the needs and challenges faced. The system design involved creating an intuitive user interface, developing document search and indexing features, and integration with document scanning technology to enable users to scan and store documents digitally. System implementation is carried out using various web technologies and software to ensure optimal functionality. Evaluation is carried out through user trials and collecting feedback to evaluate the system's effectiveness in meeting user needs and improving the efficiency of document storage and retrieval. It is hoped that the results of this research will contribute to improving the quality of archiving and information management in tutoring institutions, as well as speeding up access to required documents.